Affective Responses to Acute Resistance Exercise Performed at Self-Selected and Imposed Loads in Trained Women. Issue 11 (November 2015) - Focht, Brian C.; Garver, Matthew J.; Cotter, Joshua A.; Devor, Steven T.; Lucas, Alexander R.; Fairman, Ciaran M.
Abstract : Abstract: Focht, BC, Garver, MJ, Cotter, JA, Devor, ST, Lucas, AR, and Fairman, CM. Affective responses to acute resistance exercise performed at self-selected and imposed loads in trained women. J Strength Cond Res 29(11): 3067–3074, 2015—The purpose of this study was to examine the affective responses to acute resistance exercise (RE) performed at self-selected (SS) and imposed loads in recreationally trained women. Secondary purposes were to (a) examine differences in correlates of motivation for future participation in RE and (b) determine whether affective responses to RE were related to these select motivational correlates of RE participation. Twenty recreationally trained young women (mean age = 23 years) completed 3 RE sessions involving 3 sets of 10 repetitions using loads of 40% of 1 repetition maximum (1RM), 70% 1RM, and an SS load. Affective responses were assessed before, during, and after each RE session using the Feeling Scale. Self-efficacy and intention for using the imposed and SS loads for their regular RE participation during the next month were also assessed postexercise. Results revealed that although the SS and imposed load RE sessions yielded different trajectories of change in affect during exercise ( p < 0.01), comparable improvements in affect emerged after RE. Additionally, the SS condition was associated with the highest ratings of self-efficacy and intention for future RE participation ( p < 0.01), but affective responses to acute RE were unrelated to self-efficacy or intention. It is concluded that acute bouts of SS and imposed load RE resulted in comparable improvements in affect; recreationally trained women reported the highest self-efficacy and intention to use the load chosen in SS condition in their own resistance training; and affective responses were unrelated to motivational correlates of resistance training.